COMPOSITION AND METHOD FOR TREATING MUSCLE DECLINE ASSOCIATED WITH RENAL DISEASE OR DYSFUNCTION - PAN Yuanlong; LI Qinghong; SORRENTINO Vincenzo; KARAZ Sonia (2025)
A composition comprises medium-chain triglycerides (MCT) and at least one ingredient selected from the group consisting of: Fish oil, L-arginine, Vitamin E, Vitamin C, Vitamin B3, Vitamin B5, Vitamin B6, Vitamin B1, Vitamin B2, Folic acid, Biotin, Vitamin B12, and is formulated for use in preventing and/or treating a disease or condition associated with muscle decline in a subject in need thereof. Preferably the subject in need is an individual at risk of or suffering from a renal failure, a renal dysfunction or/and a renal disease, such as chronic kidney disease, protein-energy wasting, end-stage renal disease, kidney failure due to hospitalization in the intensive care unit, acute kidney injury, and the muscle decline is selected from muscle wasting, muscle loss due to kidney failure or dysfunction, muscle decline related to chronic kidney disease, muscle loss due to hospitalization in the intensive care unit during kidney failure, metabolic acidosis during chronic kidney disease, protein-energy wasting or combinations thereof. The method can achieve at least one result that is preventing and/or treating a disease or condition associated with muscle decline in a subject at risk of or suffering from a renal failure, a renal dysfunction or/and a renal disease. The composition and the method my be used for improving the level of at least one amino acid. Una composición comprende triglicéridos de cadena media (MCT) y al menos un ingrediente seleccionado del grupo que consiste en: Aceite de pescado, L-arginina, vitamina E, vitamina C, vitamina B3, vitamina B5, vitamina B6, vitamina B1, vitamina B2, ácido fólico, biotina, vitamina B12, y está formulada para su uso en la prevención y/o el tratamiento de una enfermedad o afección asociada con el deterioro muscular en un sujeto que lo necesita. Preferentemente, el sujeto que lo necesita es un individuo en riesgo de o que padece una insuficiencia renal, una disfunción renal y/o una enfermedad renal, tal como enfermedad renal crónica, desgaste proteico-energético, enfermedad renal terminal, insuficiencia renal debida a hospitalización en la unidad de cuidados intensivos, lesión renal aguda, y el deterioro muscular se selecciona de atrofia muscular, pérdida muscular debida a insuficiencia o disfunción renal, deterioro muscular relacionado con la enfermedad renal crónica, pérdida muscular debida a hospitalización en la unidad de cuidados intensivos durante la insuficiencia renal, acidosis metabólica durante la enfermedad renal crónica, desgaste proteico-energético o combinaciones de estos. El método puede lograr al menos un resultado que es prevenir y/o tratar una enfermedad o afección asociada con el deterioro muscular en un sujeto en riesgo de o que padece una insuficiencia renal, una disfunción renal y/o una enfermedad renal. La composición y el método pueden usarse para aumentar el nivel de al menos un aminoácido.